Integrating Threshold Concepts and Ways of Thinking and Practising: Supporting Physiotherapy Students to Develop a Holistic View of the Profession through Concept Mapping - Barradell, Sarah; Peseta, Tai (International Journal of Practice-based Learning in Health and Social Care, 2018)
The work practices of a health professional involve a complex weaving together of knowing what, knowing how, and knowing why. To help students engage with what is required for practice, educators need to have an expansive view of what it means to be a health professional in the rapidly changing real-world contexts that people inhabit today. Threshold concepts, and the complementary framework Ways of Thinking and Practising (WTP), are educational ideas that can help educators to think in those broad ways about health’s knowledge base, behaviours, and values, and how these appear in the curriculum. This article offers a case example from a pre-clinical entry-level physiotherapy subject to illustrate how threshold concepts and WTP informed what students came to understand about health professional practice. A curriculum that considers threshold concepts and WTP in combination helps both educators and students to engage with learning from multiple perspectives and to develop a connected understanding of their chosen profession. Helping students to articulate the connections between knowledge (e.g. threshold concepts) and how this knowledge is put to use (e.g. through the WTP of the profession) enables them to reconsider practice-related contexts in meaningful ways.